Stochastic Dependence in Indian Capital Markets: A Fractal Analysis of the CNX Information Technology Index - Mulligan, Robert F.; Banerjee, Debasish (Indian Journal of Finance, 2008)
This paper examines the CNX information technology index for stochastic dependence with Lo's modified rescaled-range technique. Next, five self-affine fractal analysis techniques are used for estimating the Hurst exponent, Mandelbrot-Lévy characteristic exponent, and fractal dimension. Techniques employed are rescaled-range analysis, power-spectral density analysis, roughness-length analysis, the variogram or structure function method, and wavelet analysis. Evidence against efficient valuation supports the multifractal model of asset returns (MMAR) and disconfirms the weak form of the efficient market hypothesis (EMH). Strong evidence is presented for antipersistence of this index, suggesting capital markets do not price technology securities efficiently.